Improving the Skills of MGMP Economics Teachers Malang Regency with Understanding Accurate Accounting Software in Support DUDI Needs - Izzalqurny, Tomy Rizky; Nugroho, Tatas Ridho; Muhammad; Ferdiansyah, Rifaldy Adinandra (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Service This aiming For increase understanding of Accurate accounting software to economics teachers in Malang Regency, Indonesia. Community service This overcomes gap related teacher competencies technology important modern accounting For prepare student entering the world of work. Method: Community Service Program This is done offline and online. Activities This are done to 30 MGMP Economics Teachers of Malang Regency from April -October 2024. Activities devotion consists of from observation, FGD, Accurate socialization and training as well evaluation post devotion. Practical Application: Devotion This done with do mentoring as well as Accurate certification for high school social studies teachers in Malang Regency. With thus increasing practical skills computerization Accountancy for Social Studies Teachers in High School. Conclusion: This dedication emphasizes the need for an Accurate training program, which improves teacher competence and preparation student For enter the competitive world of work.